The Philippines and South Korea : strengthening the partnership - Polo, Lily Ann G. (Diliman, Quezon City : Asian Center, 1998)
Includes bibliographical references
Keywords: Korea (South) -- Economic conditions -- 1945- -- Congresses; Korea (South) -- Economic policy -- Congresses; Korea (South) -- Foreign economic relations -- Philippines; Philippines -- Foreign economic relations -- Korea (South).